(3Pjd eTJHg GdCSeGA hGdfSHs - (3efUhQ Hf Sdje Hf efUhQ Hf aJhM GdgeOGfqj GdEScfOQGfj, hLjg GdOjf, CHh GdeXaQ, GHf GdYeGOqjI , J (B673 (3g` s; (3GHf fbWI , eMeO Hf YHO GdZfj Hf CHj HcQ Hf TLGY GdHZOGOj, eYjf GdOjf , CHh HcQ , eLO GdOjf,J (B629 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hUdGJg Ydi NjQ Ndbg eMeO NGJe GdfHjjf s
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B179s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B71 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs